Risk factors of CMV replication after allogeneic hematopoietic stem cell transplantation in children and adolescents - S. N. Shiriaev; N. V. Stancheva; Ye. V. Morozova; I. M. Barkhatov; M. Yu. Averianova; S. V. Razumova; O. V. Goloshchapov; A. B. Chukhlovin; L. S. Zubarovskaya; B. V. Afanasiev (Онкогематология)
Risk factors of CMV replication in early period after allo-HSCT (D0‑D100) were – myeloablative conditioning – HR 3.74 (1.67–8.37), р = 0.001; unrelated donor – HR 2.18 (0.86–5.26), р = 0.10; HLA-matched donor – HR 0.24 (0.05–1.06), р = 0,06. In late posttransplant period (from D+100) significant risk factors of CMV-reactivation were (according to multivariate analysis) myeloablative conditioning – HR 13.17 (3.00–57.86), р = 0.001; combination of pretransplant remission of leukemia and using cyclosporine and methotrexate – HR 0.13 (0.03–0.50), р = 0.003; combination of aGVHD and CMV reactivation in early posttransplant period – HR 2.71 (0.86–8.50), р = 0.088; using of bone marrow – HR 0.37 (0.12–1.19), р = 0.095. We revealed the significant association of aGVHD and CMV-reactivation –OR 2.91 (1.07–7.92), р=0.006, and increased rate of cGVHD in patients with CMV replication at third month after allo-HSCT OR – 2.29 (1.03–5.08), р = 0.066. We revealed a tend to decreasing relapse risk in patients who had CMV-replication – HR 0.07 (0.004–1.17), р = 0.06. Cumulative incidence of CMV-disease was 28 %. CMV-disease was lethal in 44 % patients.